Faustmann formula before Faustmann in German territorial states - Viitala, Esa-Jussi (Elsevier Science B.V., 2016)
A common perception in forest and natural resource economics is that the celebrated 'Faustmann formula' was discovered in 1849 and that the 'Faustmann rule' or Faustmann-Pressler solution to the optimal forest rotation age was derived from it a decade later by Max Robert Pressler. This paper shows that the modern perspective to the valuation of forests was presented in German territorial states much earlier than has previously been thought. In 1805 a competent forest mathematician Johann Hossfeld showed explicitly how forest value can be derived under both intermittent and sustained yield management, thus discovering the Faustmann formula. The study also shows that the close intellectual and professional connections among the first German 'forest economists' seem to have played a key role in the diffusion of modern forest economic principles from Hossfeld and his contemporaries to Faustmann and Pressler, and perhaps even more generally to modem capital theory.
Keywords: forest economy; land valuation; optimal timber harvesting; German School of forestry; history of forest economic thought; capital and investment theory; natural resource economics; forestry; rotation; science